A Feminocentric Reading Of Isabel Allende’s The House Of The Spirits (Journal of Namibian Studies : History Politics Culture, 2023)
The present research paper is entitled “A Feminocentric Reading of Isabel Allende’s The House of the Spirits. The House of the Spirits. This study establishes Isabel Allende is feminist getting reflected in her works. The study examines Allende’s women characters and establishes Isabel Allende as a feminist with reference to her novel entitled The House of the Sprits. The purpose of this paper is to analyze the image of women constructed by Allende. In Allende’s works her protagonists revamp the gender codes that have been imposed upon them, putting the feminine at the center of their action. Her women defy the patriarchal system that constrains women who do not follow prescribed gender rules. Isabel Allende’s women have proud of their sexuality, their sentimentality and their material attributes. Stemming from this feminine dimension, they re-elaborate their identity, incorporating qualities that until recently have been exclusively considered masculine: rationality courage, decision making and a strong will.Isabel Allende is the most widely translated Latin American women writer today. She is considered a marginal author and much controversy surrounds her work. One of the points of contention regarding her work concerns whether or not her novels present a feminist cosmovision.This study is an examination of feminist strategies evident in the writings of Allende’s. The investigation foregrounds the eclectic nature of Allende’s feminism as it reflects an amalgamation of post-modern literary,political and  social questions.